Increasing Investment Effectiveness In State-Owned Companies In Indonesia By Implementing Measurable And Careful Risk Management - James Vidiola (Asian Journal of Social and Humanities, 2023)
State-owned enterprises' (SOEs) performance is currently under increasing pressure. SOEs are businesses that the government controls, at least with a majority stake, in particular fields that typically concern public interests. The purpose of this study is to investigate how investment efficiency in Indonesian state-owned enterprises is affected by the implementation of precise and measurable risk management. The information utilized is board information from 25 non-monetary SOEs recorded on the Indonesia Stock Trade during the 2013-2018 period. The panel regression method is used for testing, and it was found that the joint implementation of risk management has a significant impact on investment efficiency. Linear regression is used in this study's quantitative research approach. Financial reports from non-financial SOEs that were listed on the Indonesia Stock Exchange between 2013 and 2018 were used as the data. The processed data from this study indicate that the implementation of risk management in non-financial SOEs in Indonesia between 2013 and 2018 has a significant impact on investment efficiency. The commitment to execute SOE risk the executives requires the board to deal with having choices to channel business decisions put forth to stay away from unprofitable attempts